18 SBRT for peripheral lung tumors with linac arctherapy technique: More accurate, fast and safe. (December 2018) - Darréon, J.; Annede, P.; Fau, P.; Tallet, A.; Salem, N.
Abstract : Introduction: Over the past decade, there have been significant changes in the dosimetric management of peripheral lung tumor treatments with stereotactic radiotherapy. Historically developed on linear accelerators using additional collimators, the treatments are now performed on dedicated accelerators (CyberKnife, Vero, STX TrueBeam, Versa HD for example) with dedicated equipment (positioning imagery, breathing control, contention) and dedicated beam types (Flattening Filter Free). First performed in 3D conformal radiotherapy (3D-CRT), treatments are now indicated in intensity-modulated rotational radiotherapy (VMAT)[1] . Methods: This prospective study was conducted on 30 patients with peripheral lung tumor treated by SBRT. The objective was to assess, through metrics (NC, CI, HI, Dmin PTV, and volumes of isodoses 5Gy, 10Gy, D50% and. Dpresc.[2], the possibility to improve dose distribution and decrease delivery time of SBRT with VMAT and no longer in 3D – CRT. The planning has been conducted with the RayStation v6 TPS. The scheme of radiotherapy was 48Gy in 6 fractions and the average volume of PTV was 18.3 ± 11.8cc. For each patient, the ITV was determined and the PTV achieved by applying margins of 5mm in the cranio-caudal direction and 3mm elsewhere. Two treatment plans were made: one 3D-CRT in 6MV-FFF and the other in VMAT 6MV-FFF with limitation of the movement of the blades. The optimization of the treatment plans was carried out so that 99% of the PTV volume is covered by the prescription isodose with for the 3D-CRT a collimator opening limit of 5 mm and a limit of prescription at Isocenter point of 80%. The metrics of the 30 patients were recorded and compared by a Wilcoxon test. The treatment delivery time was measured for the 3D-CRT technique and the estimate time was provided by the TPS for the VMAT. Results: The results are presented in Table 1 and Fig. 1. For almost all of the patients, the coverage of 99% of the PTV was met. Our technique allows to get a better number of conformity (p < 0.001) as well as volumes of isodose 10Gy, D50% and Dpresc. smaller (p < 0.001). The duration of treatment sessions has been reduced from 150 to 47 sec. Conclusions: The limitation of leafs movement, use of partial arcs with only photons flow variation during arc delivery achieve more consistent coverage and lower lung irradiation without interplay effect during irradiation sessions. This technique is now performed in routine.